Basic and Intermediate Igneous Activity and its Relationships to the Evolution of the Julianehåb Granite, South Greenland. - Allaart, Jan H. (Meddelelser om Grønland, 1967)
In the area investigated , situated in the eastern part of the Julianehåb granite region, six granite varieties constitute large areas between which mainly ENE-trending belts of gneiss and metamorphic supracrustals are preserved. Much of the granite probably represents anatectic pre-Ketilidian basement. Three varieties belong to the 1st episode of Ketilidian plutonism. Three younger mainly allochthonous varieties (2nd episode) were generated in connection with basic and intermediate igneous activity. One of the oldest (pre-1st episode) basic intrusive bodies was probably intruded into a granitic part of the pre-Ketilidian basement. Others occur in Ketilidian metavolcanics. Six types of calc-alkali basic and intermediate intrusives postdate the 1st episode. The metadolerites are mainly concentrated in the Julianehab granite region and are interpreted as intraorogenic. Some of the hypersthene gabbros might be contemporaneous with the metadolerites. The first phase of the 2nd episode of Ketilidian plutonism is characterised by deformation, and emplacement of allochthonous granite bodies which was controlled by older fold structures. A slow process of consolidation in the cores of the bodies eventually permitted the intrusion of the synkinematic dykes mainly concentrated there. Before these dykes were intruded the crustal conditions in the margins of the bodies and outside permitted the intrusion of the pyroxene-bearing diorites and possibly of some hypersthene gabbros during the earlier stages of the formation of the Big-feldspar granite of the second phase. The second phase is furthermore marked by migmatisation of basic and intermediate intrusives in a broad belt surrounding the southern part of the Big-feldspar granite. The latest phase of granite development, mainly confined to the eastern part of the Julianehåb granite region, is marked by emplacement of leucocratic granites and passive remobilisation of older granites followed by intrusion of the net-veined diorites and leucocratic veining. Finally swarms of slightly metamorphosed tholeiitic dykes mark the transition from plutonic to cratogenic conditions. Evidence is presented suggesting that the eastern part of the Julianehab granite region constitutes the site of the latest thermal activity in the Ketilidian mobile belt. In addition differences in crustal conditions between this part and the surrounding regions during earlier stages of the plutonic evolution are considered.